(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2002)
A hemicellulose fraction was obtained after acid hydrolysis of eucalyptus chips soaked in sulfuric acid. The hydrolysate was used as the substrate to grow Candida guilliermondii FTI 20037. The influence of the nutrients (ammonium sulfate, calcium chloride, rice bran), pH, xylose concentration in the eucalyptus chips hemicellulosic hydrolisate and fermentation time were studied indicating that the xylitol production is mainly influenced by nutrients: ammonium sulfate and rice bran; initial pH of fermentation and by the xylose concentration in the eucalyptus chips hemicellulosic hydrolisate.